Implementation of Cooperative Learning Model Type of TPS Based SAVI to Complete Student Learning Outcome of X-Grade Students on The Material of Electrolyte and Nonelectrolyte Solution in SMAN 1 Sidoarjo (Universitas Negeri Surabaya, 2018)
The aims of this research were to determine the learning implementation, student activity, and student learning outcome mastery after the implementation of cooperative learning model type of TPS based SAVI on the material of electrolyte and nonelectrolyte solution. The type of this research was pre-experiment research with the research design that has been used was